Predictors of nurse's happiness: a systematic review - Arulappan Judie; Pandarakutty Suthan; Valsaraj Blessy Prabha (Sciendo, 2021)
An acute shortage of nurses exists all over the world. Part of this shortage appears to be due to nurses' low job satisfaction, low retention, and high turnover. Happiness at work is identified as a contributing factor that determines the shortage of nurses across the world. This paper critically appraised the existing scientific articles that assessed the individual and organizational predictors of happiness among nurses.